Hurdles to development: Challenges facing Libya's post-conflict reconstruction - Betelmal, Munir Eldin Ibrahim A (AUC Knowledge Fountain, 2016)
Libya in 2016 is far away from the vision Libyans had of their country after the revolutionary war in 2011. Due to the heavy legacy of the Qaddafi regime especially the fragile or non-existence institutions and distorted national identity the process of Post-Conflict Reconstruction faced numerous hurdles. Based on intensive field work that took place in Libya during February 2016, this research discusses such hurdles, the way they were handled, and proposes possible solutions and recommendations for the way forward.